Applying Social Return on Investment (SROI) to Build a Sustainable Flood Recovery Project - Teo, Wei She; Seow , Ta Wee; Mat Radzuan, Indera Syahrul (Journal of Technology Management and Business, 2021)
Sustainability is becoming increasingly important agenda for governments, organisations and academic institutions due to the environmental and social challenges in the world today. Sustainability is no longer all about the environmental aspects but also the social and economic aspects, which can only be achieved by attaining an effective balance between these three aspects. In this regard, a study of Social Return on Investment (SROI) is critical in fostering the means to manifest the importance of these goals and it urges a new approach to define a full value of sustainability. A review of the social impact sectors identifies that SROI is the most effective approach with a solid implementation framework. Therefore, the concept of SROI is reviewed in this paper, as well as its application to government investment in flood recovery projects. This paper is prepared by conducting a series of literature reviews in order to establish a foundation for a new insight for contribution to knowledge. The researchers provides a step-by-step account of SROI implementation on a flood recovery project named â€œNew Permanent Housingâ€ (Rumah Kekal Baharu) RKB project in Kuala Krai, Kelantan. Applying the SROI methodology to the flood recovery project was feasible and provided guidance and interpretation into the projectâ€™s impact. Thus, the SROI framework can be a valuable tool for stakeholders to assess the sustainability of social investments in a sustainable environment. Keywords: SROI, sustainability, sustainable flood recovery project, social impacts